Islamic Educational Values In The Malay Pantun Tradition: A Case Study In Muara Enim Village: Introduction, Methodology, Findings, Discussion, Conclusion, References - Cukup Islamiarso; Darmanto; Yelna Septiana; Fitri Oviyanti; Maryamah (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
This study explores the Islamic educational values embedded within the Malay pantun tradition practiced by the local community in Muara Enim Village, South Sumatra. Using a qualitative descriptive approach with ethnographic methods, this research aims to uncover the moral, spiritual, and social teachings conveyed through pantun as a medium of informal education. Data were collected through observation, interviews with cultural figures and local religious leaders, and documentation of pantun texts used in daily communication and traditional ceremonies. The findings reveal that the Malay pantun not only serves as an artistic expression but also functions as a pedagogical tool promoting Islamic virtues such as humility, gratitude, sincerity, and social harmony. The study concludes that the pantun tradition represents a form of cultural da’wah, integrating Islamic values into local wisdom and reinforcing moral education in community life. Theoretically, this research contributes to the development of contemporary Islamic education by expanding the framework of value-based learning through indigenous cultural expressions. The Malay pantun tradition continues to serve as an effective medium for conveying Islamic educational values in the Muara Enim community. It transmits principles of faith, morality, and social conduct, supporting character formation and cultural identity. Despite challenges from modernization and digitalization, pantun’s rhythmic and mnemonic features enhance engagement and retention, making it a valuable tool for contemporary Islamic education. Integrating pantun into educational practices bridges tradition and modernity, ensuring the preservation and internalization of moral and spiritual values.